Base-Promoted Synthesis of O-Aryl/Alkyl N,N-Dimethylthiocarbamates Starting from Inexpensive and Environmentally Benign Disulfide - Dong, Zhi-Bing; Wang, Ming; Zhu, Hui; Liu, Xing; Chang, Cai-Zhu (Synthesis, 2017)
A series of O-aryl (alkyl) N,N-dimethylthiocarbamates were synthesized in good yields (70–77%) by reacting substituted phenols or alkyl alcohol with inexpensive, stable, and environmentally benign tetramethylthiuram disulfide (TMTD) in the presence of NaH. By avoiding use of the toxic and corrosive N,N-dialkylthiocarbamoyl chloride, the method provides a green and facile preparation for some important precursors of potentially biologically reactive compounds.
Keywords: thiocarbamate; disulfide; phenols; sodium hydride; synthetic methods